First‐trimester detection of abnormally invasive placenta in high‐risk women: systematic review and meta‐analysis. (7th February 2018) - D'Antonio, F.; Timor‐Tritsch, I. E.; Palacios‐Jaraquemada, J.; Monteagudo, A.; Buca, D.; Forlani, F.; Minneci, G.; Foti, F.; Manzoli, L.; Liberati, M.; Acharya, G.; Calì, G.
ABSTRACT: Objectives: The primary aim of this systematic review was to ascertain whether ultrasound signs suggestive of abnormally invasive placenta (AIP) are present in the first trimester of pregnancy. Secondary aims were to ascertain the strength of association and the predictive accuracy of such signs in detecting AIP in the first trimester. Methods: An electronic search of MEDLINE, EMBASE, CINAHL and Cochrane databases (2000–2016) was performed. Only studies reporting on first‐trimester diagnosis of AIP that was subsequently confirmed in the third trimester either during operative delivery or by pathological examination were included. Meta‐analysis of proportions, random‐effects meta‐analysis and hierarchical summary receiver–operating characteristics curve analysis were used to analyze the data. Results: Seven studies, involving 551 pregnancies at high risk of AIP, were included. At least one ultrasound sign suggestive of AIP was detected in 91.4% (95% CI, 85.8–95.7%) of cases with confirmed AIP. The most common ultrasound feature in the first trimester of pregnancy was low implantation of the gestational sac close to a previous uterine scar, which was observed in 82.4% (95% CI, 46.6–99.8%) of cases. Anechoic spaces within the placental mass (lacunae) were observed in 46.0% (95% CI, 10.9–83.7%) and a reduced myometrial thickness in 66.8% (95% CI, 45.2–85.2%) of cases affected by AIP. Pregnancies with a low implantation of the gestational sac had a significantly higher risk of AIP (odds ratio, 19.6 (95% CI, 6.7–57.3)), with a sensitivity and specificity of 44.4% (95% CI, 21.5–69.2%) and 93.4% (95% CI, 90.5–95.7%), respectively. Conclusions: Ultrasound signs of AIP can be present during the first trimester of pregnancy, even before 11 weeks' gestation. Low anterior implantation of the placenta/gestational sac close to or within the scar was the most commonly seen early ultrasound sign suggestive of AIP, although its individual predictive accuracy was not high. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.